The relation between splanchnic ischaemia and intestinal damage in necrotising enterocolitis. Issue 6 (5th April 2016) - Schat, Trijntje E; Heida, Fardou H; Schurink, Maarten; van der Laan, Michelle E; Hulzebos, Christian V; Bos, Arend F; Kooi, Elisabeth M W; Hulscher, Jan B F
Abstract : Objectives: The underlying pathophysiology of necrotising enterocolitis (NEC) remains incompletely understood, particularly the role of intestinal perfusion. We aimed to determine the relation between cerebral and splanchnic fractional tissue oxygen extraction (FTOE), a marker for tissue underperfusion, with intestinal fatty acid-binding protein in plasma (I-FABPp), a marker for intestinal damage, in infants with NEC. Furthermore, we investigated the combined courses of cerebral and splanchnic FTOE values and I-FABPp levels in uncomplicated (conservative treatment) and complicated NEC (surgery or death). Design: This study was part of a prospective observational cohort study. Patients: We included 19 preterm infants with NEC (9 uncomplicated, 10 complicated). Interventions: Using near-infrared spectroscopy, we measured regional cerebral and splanchnic tissue oxygen saturations continuously for 48 h after NEC onset. We measured I-FABPp levels simultaneously. Main outcome measures: We used Spearman correlation tests to calculate correlation coefficients between FTOE values and I-FABPp levels in uncomplicated and complicated NEC. Results: Median (range) gestational age was 28 (25–36) weeks and median (range) birth weight was 1290 (740–2400) g. Cerebral and splanchnic FTOE values correlated strongly with I-FABPp levels (rho between .745 and 0.900; p<0.001–0.037) during the first 16 h after NEC onset. Thereafter, in uncomplicated NEC, splanchnic FTOE values increased while I-FABPp levels decreased concomitantly. In complicated NEC both splanchnic FTOE values and I-FABPp levels decreased. Conclusions: Combining cerebral and splanchnic FTOE values with I-FABPp levels, gives insight in the pathological chain of events resulting in progression or recovery of intestinal ischaemia in NEC. Trial registration number: NTR3239.